STUDY OF PUBLIC TRANSPORTATION SERVICE LEVEL IN MAJALENGKA CITY - Yudi Herdiana; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2024)
In Majalengka, there are only a few public transportation options, including Angkutan Kota (public minivans), online motorcycle taxis (Ojek Online), and even traditional becak (pedicabs) can still be found in the city. The absence of trains and the limited number of public minivans may contribute to the lack of attractiveness of public transportation in Majalengka. Even in urban areas of Majalengka, some regions cannot be reached by public minivans. This study aims to evaluate the level of public transportation service to the community, providing evidence of the quality of public transportation services in Majalengka Kota. The research methodology employed in this study is quantitative. Majalengka Kota serves as the central government area of Kabupaten Majalengka, making it the hub of activities for its residents. This is due to the presence of various facilities that make Majalengka Kota a centre for activities, including recreational centres, food centres, favourite schools, etc. In conclusion, the Customer Satisfaction Index (CSI) in this study is 68%, which falls into the satisfactory category. The comparison of the importance and performance levels of transportation services shows a minimal GAP of 0.094, which is still positive, indicating a satisfactory and secure level of service. Lastly, the Importance Performance Analysis (IPA) graph identifies two variables, Administration (A) and Going (G), as the main priorities for improvement. The government should address these areas to anticipate and enhance future transportation services.